A New Semi-Synthetic Sapogenol Derivative Inducing Regulated Necrosis - Üner, Göklem; Bedir, Erdal; Ballar Kırmızıbayrak, Petek; Üner, Göklem; Bedir, Erdal (Georg Thieme Verlag, 2019)
Since saponin’s antitumor potency is relatively weak, researchers focus on their semi-synthetic modification to obtain structures with higher potencies. With the same motivation, we prepared a cytotoxic sapogenol derivative (AG-08) from cycloastragenol. Our preliminary studies revealed that AG-08 induced primarily necrotic cell death along with autophagic inhibition. Furthermore, immunoblotting experiments demonstrated that AG-08 promoted cleavage of various proteins such as ATGs, p62, and PARP-1.
67th International Congress and Annual Meeting of the Society-for-Medicinal-Plant-and-Natural-Product-Research (GA) -- SEP 01-05, 2019 -- Innsbruck, AUSTRIA